Precursor evolution and growth mechanism of BTO/YBCO films by TFA-MOD process - 王洪艳 丁发柱 古宏伟 张腾 彭星煜 (Chinese physics B, 2014)
In this study, BaTiO3 （BTO）-doped YBCO films are prepared on LaA103 （100） single-crystal substrates by metal- organic decomposition （MOD） using trifluoroacetate （TFA） precursor solutions. The critical current density （Jc） of BTO/YBCO film is as high as 10 MA/cm2 （77 K, 0 T）. The BTO peak is found in the X-ray diffraction （XRD） pattern of a final YBCO superconductivity film. Moreover, a comprehensive study of the precursor evolution is conducted mainly by X-ray analysis and μ-Raman spectroscopy. It is found that the TFA begins to decompose at the beginning of the thermal process, and then further decomposes as temperature increases, and at 700 ℃ BTO nanoparticles begin to appear. It sug- gests that the YBCO film embedded with BTO nanoparticles, whose critical current density （Jc） is enhanced, is successfully prepared by an easily scalable chemical solution deposition technique.